Fluorescent Thiol-Derivatized Gold Clusters Embedded in Polymers - G. Carotenuto; S. De Nicola; L. Nicolais (Advances in Materials Science and Engineering)
Owing to aurophilic interactions, linear and/or planar Au(I)-thiolate molecules spontaneously aggregate, leading to molecular gold clusters passivated by a thiolate monolayer coating. Differently from the thiolate precursors, such cluster compounds show very intensive visible fluorescence characteristics that can be tuned by alloying the gold clusters with silver atoms or by conjugating the electronic structure of the metallic core with unsaturated electronic structures in the organic ligand through the sulphur atom. Here, the photoluminescence features of some examples of these systems are shortly described.